The Use of Collaborative Strategic Reading to Teach Reading - Shally Mursalina (Universitas Syiah Kuala, 2018)
The objective of this study was to find out the significant effect and analyze students’ perspective on the advantages and disadvantages of using Collaborative Strategic Reading (CSR). The population was all of the ninth grade students of MTsN 5 Aceh Utara. The sample was the students of class IX-1. This research used mix-method approach and the data were collected through test and interview. Thisresearchfocused on three aspects in reading comprehension mainly in identifying main idea, finding supporting details and making reference. The writer conducted pretest, treatment and post-test to collect data. The result of this study shows that the mean score of pre-test was 60 and the mean score of post-test was 64.44. While the gain score was 4.44. It shows that there was an improvement in students’ reading achievement after they were given the treatment. Moreover, the analysis of t-test showed that t-value t-table or 4.58 1.70 at the level of significance 0.05 with the degree of freedom (df) 26. It means that the alternative hypothesis (Ha) is accepted. Furthermore, CSR could give the students benefits in promoting the students’ self-esteem to work cooperatively in group. Thus, CSR has an influence to improve students’ reading achievement in teaching reading.